Electrocardiographic changes that identify patients at risk for atrial fibrillation - Ribeiro Moreira, Dalmo Antonio (JOURNAL OF CARDIAC ARRHYTHMIAS, 2018)
The electrocardiogram is a graphical recording of cardiac electrical activity. The waves in an electrocardiogram are obtained by means of electrode-cables positioned in a conventional way on the body surface and for this reason, their characteristics, including both duration and morphology, are well established. Any changes in these waves may indicate electrical activity changes of the atria and/or ventricles. This concept is important not only for diagnosing heart muscle disease but also for staging the disease and establishing prognosis. Atrial fibrillation is a frequent arrhythmia whose incidence increases with age and with the accumulation of risk factors related to its origin. Several diseases which develop throughout a patient’s lifetime cause atrial tissue lesions and atrial electrical and structural derangements whose manifestations may be modifications of p wave characteristics such as its morphology and duration, as well as its relationship with the PR interval. These changes, when detected, may be useful for the early identification of patients most likely to have atrial fibrillation and their presence, along with clinical scores that define “sicker” individuals, have been shown to be a useful ally in the clinical management of this population. The purpose of this study is to update these concepts for the clinical practice.